Analysis of Studying Passages on the Piano Requiring Speed and Different Rhythm Patterns - Zeynep Oya Bıyıklıoğlu (Konservatoryum)
When playing the piano, both beginner and advanced-level pianists occasionally suffer from problems of playing a consistent rhythm even in passages that require speed. This study investigates the benefits of group repetitive exercises for overcoming the problem of playing passages that require speed with a consistent rhythm. The study was conducted with 50 second-year students in the Fine Arts Department Music Education Department of Marmara University Atatürk Faculty of Education. The 25 students in the experimental group were made to practice Czerny’s Op. 599, No. 58 using exercise drills for the 1/16th notes in the right hand, while the control group was told to play the same etude without performing any practice drills. Separate t tests were conducted for the variables of correct note, correct rhythm, and playing without pause. As a result, a significant difference was found in favor of the experimental group.